The Influence Of Education And Training On Employee Performance At The Class I Tpi Bandar Lampung Immigration Office - Citra Amalia; M. Yusuf S Barusman (Cita konsultindo, 2025)
This study analyzes how the influence of Education (X1) and Training (X2) affects employee performance (Y) at the Class I TPI Bandar Lampung Immigration Office. The technique used is a quantitative approach, where data is obtained from 44 samples from 80 populations. The purpose of this study is to analyze the influence of Education and Training partially and simultaneously. The study states that X1 has a very big influence on Y, X2 has no influence on Y, and X1 and X2 simultaneously have a positive and significant influence on Y. The leadership of the Class I TPI Bandar Lampung Immigration Office should pay attention to factors that can influence employee performance,This effort is able to increase overall employee productivity and performance.